Realisasi Fonem Vokal Bahasa Indonesia - Meta Agesta Kalih Purwasih; Muhammad Septian; Dio Armando (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
The purpose of this study this study describes the realization form of vowel phoneme, consonant phoneme in Indonesian language. Through this research, it is hoped that it can be useful for the Indonesian speakers, especially educators and students. In addition,In addition, this research is expected to inspire linguistic experts to examine more comprehensively related to the realization of Indonesian vowel phonemes. This research uses descriptive qualitative method by using a collective case approach study (collection case study). Data collection using observation, listening and note-taking techniques. The instruments we use in this research data collection itself are equipped with notes and scientific journals. complete with notes and scientific journals. In this study can conclude that (1) the realization of Indonesian vowel phonemes consists of 2 kinds, namely (a) in accordance with the rules and (b) in accordance with the rules. kinds, namely (a) in accordance with the rules and (b) deviating from the rules; and (2) deviations in the realization of vowels are in the vowels /i/, /u/, and /o/ in the closing position and in derived words. Deviations also The reflection of the realization of the vowel /u/ also occurs in abbreviations of Indonesian original words. Indonesian original words. There are deviations in the realization of the vowel /e/ that cause disparity of meaning. but there are also those that do not cause disparity of meaning. meaning.